2018
DOI: 10.1021/acsami.8b14480
|View full text |Cite
|
Sign up to set email alerts
|

Photostability and Photodegradation Processes in Colloidal CsPbI3 Perovskite Quantum Dots

Abstract: All-inorganic CsPbI3 perovskite quantum dots (QDs) have attracted intense attention for their successful application in photovoltaics (PVs) and optoelectronics that are enabled by their superior absorption capability and great photoluminescence (PL) properties. However, their photostability remains a practical bottleneck and further optimization is highly desirable. Here, we studied the photostability of as-obtained colloidal CsPbI3 QDs suspended in hexane. We found that light illumination does induce photodeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 31 publications
5
115
0
Order By: Relevance
“…By contrast, the k nr value first increases slightly due to the increasing number of defects caused by the heterovalent doping, [48] but then gradually decreases when the x value is over 3.5%, which could be ascribed to the reduction of surface metallic Pb 0 defect states as shown in the XPS results (see Figure 1c). [34] It is believed that the introduction of shallow energy levels and curing of the intrinsic structural disorder are the main reasons of improved PLQY in Cd 2+ and Mg 2+ doped CsPbCl 3 . [14,19,49] We find that the radiative recombination rate k r exhibits a more significant change according to the PL decay while the nonradiative recombination rate k nr only experiences a slight change.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the k nr value first increases slightly due to the increasing number of defects caused by the heterovalent doping, [48] but then gradually decreases when the x value is over 3.5%, which could be ascribed to the reduction of surface metallic Pb 0 defect states as shown in the XPS results (see Figure 1c). [34] It is believed that the introduction of shallow energy levels and curing of the intrinsic structural disorder are the main reasons of improved PLQY in Cd 2+ and Mg 2+ doped CsPbCl 3 . [14,19,49] We find that the radiative recombination rate k r exhibits a more significant change according to the PL decay while the nonradiative recombination rate k nr only experiences a slight change.…”
Section: Resultsmentioning
confidence: 99%
“…[ 39,45 ] However, the capping reagents are easily removed, resulting in surface defects and degradation of PQDs. [ 46 ] It is expected that through interaction between nonfullerene Lewis base and the Pb ion Lewis acid, nonfullerene acceptors could stabilize the PQDs in case of detachment of the capping reagents.…”
Section: Figurementioning
confidence: 99%
“…For neat FOIC, the peaks at 1699 and 2217 cm ‐1 are attributed to the symmetric stretching vibrations of CO and CN bonds, respectively. [ 42 ] For neat PQDs, the peaks at 1379 and 1468 cm ‐1 are attributed to antisymmetric and symmetric stretching vibrations of COO − , and the peak at 1641 cm ‐1 is assigned to the N–H bending vibration, [ 46 ] which indicated that the PQDs have caping reagents coming from precursors (oleic acid and oleylamine). We normalized the peak at 1540 cm ‐1 (stretching vibrations of CC bonds) of FOIC and FOIC:PQDs blend in order to distinguish the differences between them.…”
Section: Figurementioning
confidence: 99%
“…Mixing 2D/3D perovskites also produced passivation of the traps and protection toward humidity. [32] We believe that the surface passivation of perovskites with another semiconductor shell is a particularly promising approach to increase the stability of perovskites under continuous irradiation. [31] In general, mixing different cation and anions seems to improve the structural stability of perovskites and prevents undesired phase transitions.…”
Section: The Challengesmentioning
confidence: 99%